Reinventing subjectivity: China Miéville’s Un Lun Dun and the child reader - Sanders, Joe S. (My University, 2009)
Miéville’s first novel for young readers was an instant success with scholars of children’s literature. Its violation of bourgeois models of subjectivity fit nicely with the current discourse about leftist literature and its ability to correct some of the most persistent problems of manipulation and moralism in children’s literature. The novel ingenuously fulfills many of the calls to action by scholars, but it also exceeds those calls by imagining a subjectivity for language and books themselves. The result is both a model of readers who avoid complacency and a kind of language against which readers can and must argue.
Keywords: Miéville, China; Un Lun Dun; Children’s literature; Leftist literature